RTS,S/AS01 vaccine (Mosquirix™): an overview - Laurens, Matthew B. (Human vaccines & immunotherapeutics, 2020)
Malaria is an illness caused by Plasmodium parasites transmitted to humans by infected mosquitoes. Of the five species that infect humans, P. falciparum exacts the highest toll in terms of human morbidity and mortality, and therefore represents a major public health threat in endemic areas. Recent advances in control efforts have reduced malaria incidence and prevalence, including rapid diagnostic testing, highly effective artemisinin combination therapy, use of insecticide-treated bednets, and indoor residual spraying. But, reductions in numbers of cases have stalled over the last few years, and incidence may have increased. As this concerning trend calls for new tools to combat the disease, the RTS,S vaccine has arrived just in time. The vaccine was created in 1987 and began pilot implementation in endemic countries in 2019. This first-generation malaria vaccine demonstrates modest efficacy against malaria illness and holds promise as a public health tool, especially for children in high-transmission areas where mortality is high.